DISPUTE RESOLUTION OF FOREIGN DIRECT INVESTMENT IN CHINA - Fiska Silvia Raden Roro (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2012)
Praktek korupsi di zaman modern ini masih melukai upaya penyelesaian sengketa penanaman modal asing di Indonesia. Namun sebenarnya pada saat ini Indonesia sedang menjadi negara tujuan menarik bagi kegiatan penanaman modal asing, terutama bagi produsen barang-barang manufaktur, hal ini tidak lain disebabkan karena sumber daya alam Indonesia yang mendukung kegiatan perekonomian. Dalam tulisan ini ditujukan agar dapat memacu pengembangan sistem hukum di Indonesia terutama dalam hal penanaman modal asing dan untuk membahas mengenai bagaimana penyelesaian sengketa pada penanaman modal asing dalam kaitannya dengan Chinese Regime dan pengaruh akan budaya Cina pada metode negosiasi, mediasi, arbitrasi. Dalam penulisan ini juga dibahas mengenai upaya penyelesaian sengketa melalui litigasi, penegakan hukum dari putusan arbitrase asing serta penegakan hukum terhadap hasil keputusan pengadilan asing, dalam kaitannya dengan Chinese Regime.Corruption activity in this modern era keeps hurting the implementation of foreign investment in Indonesia, especially for the dispute settlement aspect. Unfortunately, today, Indonesia is one of the interesting place for foreign investment destination, especially for consumer goods manufacturers. This situation happened because of Indonesia’s great resources which is totally supportive to business development activity. This article was intended to spur the development of Indonesia’s legal system, especially about foreign investment, and also to explain how the dispute resolution on foreign investment in Chinese Regime perspective, including considerations of how Chinese culture and settlement in foreign investment, methods of negotiation, mediation, arbitration. It will also be discussed how the practice of the settlement of disputes through litigation also the enforcement of foreign arbitral awards and the enforcement of a foreign court related to Chinese Regime.